Stable physical activity tracking during children's guided active play - Moghaddaszadeh, Asal; Taqvi, Urooj; Lee, Caitlin; Lee, Erran; Belcastro, Angelo (Frontiers in Sports and Active Living, 2022)
Objective: Children’s physical activity (PA) behaviour shows poor tracking statistics during development, The large variability observed for PA in different settings (in/out of school; habitual PA) contributes to the low tracking. This study examines the stability of PA behaviour over a one-year interval for school-aged children when using guided active playing of cooperative (social) games during community summer day-camp programs. Methods: Children registered in two consecutive year 5-day summer camps were assessed for growth, health, and fitness variables and PA participation in guided active play sessions. PA participation was assessed by accelerometry during a self-paced guided active play program (1 hr.d-1 on 2 d.wk-1). Tracking statistics included Spearman rank order correlations and Kappa statistics for agreement scores using percentile ranks between the Baseline and 1-year follow up. Results: Children’s developmental changes from Baseline to year 1 showed age related group changes for physical activity with moderately high tracking (r=0.88, p=0.001) and moderate agreement (k=0.54). Physical activity behaviour tracked at each age group (i.e., 7-8 yrs, 8-9 yrs, 9-10 yrs, 10-11 yrs and 11-12 yrs) and showed strong coefficients (p< 0.05), except for the 9-10yrs children. During the 1-yr interval the intensity (moderate-vigorous physical activity) showed moderate tracking (0.74, p=0.003) and moderate agreement (0.47, p=0.02). Conclusion: PA participation for school-aged children is stable when participating in self-paced guided active play. Evidence suggests that a guided active play approach to track children’s physical activity participation may also promote stronger relationships between cardiometabolic risk factors during development.